The problem of orthodoxy: evangelicals at the crossroads of truth and power - Blanco, Michael H. (Lexington Books, 2024)
"This book examines the history and fallout of Christian orthodoxy, especially evangelical orthodoxy in the United States. It concludes that orthodoxy functions as an ideology of power as much as a barometer of "correct belief" and that understanding this dimension of orthodoxy can help inhibit its most dangerous outcomes"--